Harnessing aggregation-induced emission property of indolizine derivative as a fluorogenic bioprobe for endoplasmic reticulum. (April 2022) - Arun, V.; Choi, Sang-Kee; Han, Ji Hye; Choi, Hongseo; Kim, Hyung-Mo; Kim, Wook; Choi, Junwon; Kim, Jonghoon; Kim, Eunha
Abstract: For fluorogenic bioimaging of the endoplasmic reticulum, a new aggregation-induced emission luminogen (AIEgen) core skeleton was conjugated with glibenclamide. Click chemistry was successfully employed for the efficient conjugation between azide-modified glibenclamide and alkyne-containing indolizine core skeleton to generate Aru68 . When the volume fraction of water is increases in the solution of Aru68 in water and DMF induced aggregates formation and simultaneous increase of fluorescence intensity up to 100-fold was observed. Solvatochromism and restriction of molecular motion study by perturbation of solvent polarity index and volume fraction of glycerin in glycerin/methanol mixture provided a mechanistic insight into the turn-on phenomenon of Aru68 as AIEgen. The final bio-imaging demonstration of Aru68 in live cell conditions revealed great potential not only of the probe for wash-free bioimaging of the endoplasmic reticulum but also of the indolizine core skeleton for efficient fluorogenic bioprobe development based on aggregation-induced emission processes. Highlights: Conjugation between indolizine derivatives and glibenclamide resulted Aru68. Solvatochromism study confirmed intramolecular charge transfer takes place in Aru68. Increasing the solvent viscosity of Aru68 increase the emission intensity 130-fold. Simultaneous emission intensity increase was observed with aggregate formation. Aru68 allows successful fluorogenic labeling of ER in live cells.